The Effect of Work-Life Balance and Workload on Burnout in Employees at a Sugar Processing Company in West Java - Hilman Wikhyat; Dharliana Hardjokowikarto; Juwita Juwita (CV. AFDIFAL MAJU BERKAH, 2026)
The rapid development of marketplaces as digital business actors in electronic transactions has significantly increased technology-based economic activities in Indonesia. However, the dominance of standard form contracts that are unilateral and exclusionary has created an imbalance in bargaining positions between business actors and consumers. This study focuses on examining how the construction of marketplace liability as digital business actors is formulated in electronic transaction agreements, as well as evaluating the effectiveness of the consumer protection legal regime in Indonesia in regulating such practices comprehensively. The findings indicate that, normatively, the legal framework through the Consumer Protection Law, the Electronic Information and Transactions Law, and their implementing regulations has regulated the prohibition of liability limitations and the obligations of electronic system providers. However, in practice, marketplaces tend to utilize standard clauses to shift risks to sellers and consumers, resulting in a deviation between norms (das sollen) and practice (das sein). Moreover, the factual role of marketplaces, which includes controlling transaction systems, managing funds, and determining dispute resolution mechanisms, demonstrates that marketplaces can no longer be positioned as passive intermediaries. Rigid and incomplete consumer protection often results in unfair compensation. This situation demands reforming marketplace accountability through stronger regulations, limiting conditions that harm consumers, and providing an independent dispute resolution system for fairness.